2012
DOI: 10.1210/er.2011-1050
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and Endocrine-Disrupting Chemicals: Low-Dose Effects and Nonmonotonic Dose Responses

Abstract: For decades, studies of endocrine-disrupting chemicals (EDCs) have challenged traditional concepts in toxicology, in particular the dogma of "the dose makes the poison," because EDCs can have effects at low doses that are not predicted by effects at higher doses. Here, we review two major concepts in EDC studies: low dose and nonmonotonicity. Low-dose effects were defined by the National Toxicology Program as those that occur in the range of human exposures or effects observed at doses below those used for tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

71
1,753
3
40

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,557 publications
(1,908 citation statements)
references
References 785 publications
71
1,753
3
40
Order By: Relevance
“…Similarly, nutrients such as nitrogen are required for growth, but in high concentrations can lead to nutrient toxicity, such that performance of primary producers generally peaks at intermediate nutrient concentrations (Pilon‐Smits, Quinn, Tapken, Malagoli, & Schiavon, 2009; Figure 1b). Even some toxins can have beneficial effects at very low doses and others exhibit complex nonlinear effects based on concentration and an organism's ability to counteract the negative impacts (Calabrese & Baldwin, 2003; Vandenberg et al., 2012; Figure 1d).…”
Section: Stressors Resources and The Cost‐benefit Continuummentioning
confidence: 96%
“…Similarly, nutrients such as nitrogen are required for growth, but in high concentrations can lead to nutrient toxicity, such that performance of primary producers generally peaks at intermediate nutrient concentrations (Pilon‐Smits, Quinn, Tapken, Malagoli, & Schiavon, 2009; Figure 1b). Even some toxins can have beneficial effects at very low doses and others exhibit complex nonlinear effects based on concentration and an organism's ability to counteract the negative impacts (Calabrese & Baldwin, 2003; Vandenberg et al., 2012; Figure 1d).…”
Section: Stressors Resources and The Cost‐benefit Continuummentioning
confidence: 96%
“…Environmentally relevant doses of BPA (at or below 5-50 g/kg) was reported to have estrogenic effects [13,16]. In addition to this, numerous studies suggested that BPA could bind to several kinds of receptors including androgen receptors, thyroid receptors, orphan estrogen-related receptor gamma (ERR␥) [17] and RXRs [12,18].…”
Section: Introductionmentioning
confidence: 99%
“…after the long-term exposure to environmental observed concentrations (ng/L) aggravate these worries (Hotchkiss et al, 2008;Vandenberg et al, 2012;Zha et al, 2007). Particularly, steroid estrogens (both natural and synthetic) and phenolic xenoestrogens receive more attention because of their non-ignorable estrogenicities and widespread applications (Peng et al, 2006).…”
Section: Introductionmentioning
confidence: 99%